Perivascular RELMα-positive synovial macrophages recruit monocytes at the onset of inflammatory arthritis - Schonfeldova, Barbora; Chibwana, Marah; Gentek, Rebecca; Zec, Kristina; Udalova, Irina A. (Frontiers in Immunology, 2025)
Macrophages, monocytes and neutrophils are major types of myeloid cells involved in inflammatory diseases, such as rheumatoid arthritis (RA). Recent scRNA-seq studies identified a remarkable diversity of synovial macrophages but, with the exception of lining macrophages, their geographical location and specific roles remain largely unexplored. Here, we localized the RELMα-positive macrophages, predicted to produce high levels of monocyte-recruiting chemokines, to the synovial interstitium and more specifically, to the vicinity of interstitial blood vessels. Using complementary reporter mouse models, CCL2mCherry to label CCL2-producing cells, and CCR2CRE/mKate2 marking CCR2 expressing monocytes, we demonstrated that RELMα-positive perivascular macrophages secrete CCL2 assisting in the recruitment of monocytes predominantly to the synovial interstitium at the onset of antigen-induced arthritis. The inflamed synovial environment guides the differentiation of the recruited monocytes into tissue-resident macrophages, including but not limited to macrophages expressing VSIG4, a characteristic marker of lining macrophages. Thus, RELMα-positive macrophages orchestrate monocyte recruitment to the synovium during articular inflammation, contributing to a local replenishment of synovial lining macrophages.